Prevalence, Complications and Outcome of Clandestine Abortion in Rural Eastern Area of Democratic Republic of the Congo (D.R.C) - , Michel Kyembwa Mulyumba; , Michel Kalongo Ilumbulumbu; , Tecla Katungu Kitamwivirirwa; , Joel Kambale Ketha (Archives of Current Research International, 2018)
Background: The number of pregnancies per year in the world is about 210 million, of which 182 million are in developing countries. The abortion reflects the significance of unplanned pregnancies and unsafe abortion is one of the biggest contributors to global maternal mortality. The objective of this study was to investigate the prevalence, complications and outcome of clandestine abortions in Referral Health Center of Eringeti, in the Oicha health area in the DRC. Methods: This was a prospective cross-sectional study, which took place from 1st November 2016 to 30th November 2017 on 52 patients received in the department of gynaecology and obstetrics of the Eringeti Referral Health Center in DRC following the complications related to abortion. Results: The prevalence of the clandestine abortion was from 45.61% in the Eringeti Referral Health Center. The abortive had largely set the age below 20 years, no level of study; they were farmers and bachelors. Among 86.5% of them were nulliparous and first pregnancies and pregnancy had largely left the age less than 12 weeks. The abortions were carried out at the homes of the patients in 96.2% of cases and traditional decoctions and pharmaceutical products obtained outside of health facilities were more used. The genital bleeding, uterine perforation and endometritis were major complications listed and death was recorded related to the post septicemia endometritis not tidy at home. Conclusion: The clandestine abortion is a major problem of public health in the Oïcha Health area in the North Kivu Province in DRC. The awareness on responsible sexuality and family planning would be important in the decrease of this practice regarded like illegal in our country.